2013
DOI: 10.1007/s00429-013-0683-7
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging of hippocampal network plasticity

Abstract: Diffusion tensor imaging (DTI) has become a valuable tool to investigate white matter integrity in the brain. DTI also gives contrast in gray matter, which has been relatively little explored in studies assessing post-injury structural abnormalities. The present study was designed to compare white and gray matter reorganization in the rat hippocampus after two epileptogenic brain injuries, status epilepticus (SE) and traumatic brain injury (TBI), using ex vivo high-resolution DTI. Imaging was performed at 6-12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 59 publications
5
44
1
1
Order By: Relevance
“…Recently it was recognized that DTI can detect abnormalities in gray matter as well as in white matter. 91 Results from the present study demonstrated the feasibility of using DTI as a detailed biomarker to quantify the severity and regional extent of injury and repair after infant TBI. Additional detailed regional analyses to clarify the extent of microstructural abnormalities throughout the brain using this model are underway.…”
Section: Discussionmentioning
confidence: 59%
“…Recently it was recognized that DTI can detect abnormalities in gray matter as well as in white matter. 91 Results from the present study demonstrated the feasibility of using DTI as a detailed biomarker to quantify the severity and regional extent of injury and repair after infant TBI. Additional detailed regional analyses to clarify the extent of microstructural abnormalities throughout the brain using this model are underway.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, our ROI analysis of hippocampal gray matter using DTI is relatively new. Hippocampal plasticity via manual ROI delineation has been examined in rodents (Sierra et al ., ) and in humans (Goubran et al ., ). These studies did not focus on the dendritic regions but included all hippocampal structures.…”
Section: Discussionmentioning
confidence: 99%
“…In the epileptic hippocampus of several rodent epilepsy models DWI successfully identified changes of water diffusion, which is discussed to primarily relate to mossy fiber sprouting and reorganization of myelinated axons (Kharatishvili et al, 2007; Kuo et al, 2008; Laitinen et al, 2010; Sierra et al, 2015a, 2015b; Salo et al, 2017). However, it is important to note that the above mentioned epilepsy models do not fully reflect the histopathological hallmarks of pharmacoresistant mTLE (i.e., unilateral HS including GCD) complicating a translation to the human disease.…”
Section: Discussionmentioning
confidence: 99%